Effect of headlocks on milk production and feed intake of dairy cattle - Smith, John F., 1962-; Harner, Joseph P.; DeFrain, S.E.; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Cows previously trained with headlocks did not increase milk production or feed intake when headlocks were removed. Twoyear- old and older cows did not differ in response to headlocks and neckrails. Prudent use of headlocks increases labor efficiency of a commercial dairy. Managing a dairy without headlocks is a challenge because cows must be sorted and worked off the milking parlor flow. In the case of large milking parlors, it may be necessary to process 50-200 cows per hour. Depending upon the treatment facilities, this number of cows may create a bottleneck in the dairy. For many routine procedures, headlocks offer the simplest and most cost-effective alternative. It is important to note that headlocks can be mismanaged. This is especially true during summer months. Locking up cows for extended periods without access to water or shade may have adverse effects during summer heat stress. It is important to minimize lock-up time. Consideration should also be given to training heifers to headlocks prior to calving. It is very likely that untrained heifers may be reluctant to be placed in headlocks. If this occurs, intake could be limited during their first exposure to headlocks. If heifers are not trained to headlocks prior to calving, one should determine if they should be locked-up each day during the first week of lactation. Headlocks can be successfully used on a dairy. The critical question is how will they be managed. Successful managers of headlocks minimize restraint time, push-up or feed pens often (6- 8 times per day), and avoid use of headlocks during late morning and afternoon hours during the summer months.
Keywords: Dairy; Cow comfort; Restraint; Stress